Late Neolithic and post-Neolithic settlements and burial grounds in the TPC Area at Çatalhöyük: The research project of the archaeological team of Adam Mickiewicz University in Poznań - Filipowicz, Patrycja; Harabasz, Katarzyna; Hordecki, Jędrzej; Joka, Karolina; Marciniak, Arkadiusz (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
The chapter presents the results of the research project conducted by the team of archaeologists from Adam Mickiewicz University at the World Heritage site of Çatalhöyük in Turkey. The section of this large Neolithic settlement located in the uppermost part of the south eminence of East mound is named the Team Poznań Connection (TPC) Area and was excavated in the years 2012-2017. The unearthed stratigraphic sequence is dated to the period from ca. 6350 to 6000 BC. The project led to the discovery of nine Late Neolithic houses with associated built-in structures and numerous burials. The paper outlines the most important discoveries in house architecture, burial practice, and material culture. The research has contributed significantly to a better understanding of the last centuries of the settlement’s occupation, as well as enhanced our knowledge of the Near Eastern Neolithic. This paper provides an overview of the major transformations of Neolithic lifeways in this period. In addition to architecture, the organization of space, burial practices, and material culture, the changes also affected farming, husbandry practices, landscape exploitation, procurement of raw materials, exchange patterns, demography, and social organization. The paper also provides an overview of the Hellenistic settlement as well as the Ottoman burial ground located above the Neolithic strata.
Keywords: Çatalhöyük, Anatolia; Hellenistic period; Late Neolithic; Ottoman period